Association between Neutrophil-Lymphocyte Count Ratio and Matrix Metalloproteinase-9 in Patients with Acute Myocard Infarction - Tiksnadi, Badai Bhatara; Akbar, Muhammad Rizki; Yahya, Achmad Fauzi; Hidayat, Syarief; Purnomowati, Augustine; Aprami, Toni Mustahsani (Majalah Kedokteran Bandung, 2019)
The correlation between metalloproteinase-9 (MMP-9) level and neutrophil-lymphocyte count ratio (NLCR) in AMI patients has not been studied despite the fact that they are both known to predict ventricular remodeling. This study aimed to evaluate the correlation between the MMP-9 level and NLCR in patients with acute myocardial infarction. A cross-sectional study was conducted by recruiting acute coronary syndrome patients (onset within 24 hours) who were admitted to the emergency department in several hospitals around Bandung during October-December 2012. The relationship between the MMP-9 level and NLCR was analyzed using Pearson correlation test. Linear regression analysis was used to measure the strength of NLCR in MMP-9 level prediction. Thirty seven patients aged 55.8 + 11 years old were included in this study with mostly male patients (78%). Seventy-six percents of the sample were ST-elevation myocardial infarct (STEMI) patients with the onset of symptoms of 6 (3-14) hours. The mean lymphocyte-neutrophil ratio was 5.24 (1Ïƒ±2.4) and the MMP-9 plasma concentration was 370 (240-530) ng/mL. One-sided Pearson correlation showed a positive correlation between the two variables (r=0.44, p=0.003). The linear regression analysis conceived the formula of MMP-9 = 40.87 (NLCR) + 211.3 which was used to show the relationship between the MMP-9 level and lymphocyte-neutrophil ratio. There was a positive moderate correlation between the MMP-9 level and NLCR in patients with AMI. Linear regression analysis shows that NLCR is the only independent variable to predict the MMP-9 plasma level. Key words: Acute myocardial infarct, left ventricular remodeling, matrix metalloproteinase (MMP)-9, neutrophyl-lymphocyte count Ratio (NLCR) Korelasi Rasio Neutrofil-Limfosit (NLCR) dengan Kadar Matriks Metaloproteinase-9 pada Penderita Infark Miokardium Akut Korelasi antara matriks metaloproteinase-9 (MMP-9) dan rasio netrofil-limfosit masih belum pernah dipelajari, meskipun kedua variable tersebut diketahui dapat memprediksi remodeling ventrikel kiri. Studi ini bertujuan mengevaluasi korelasi antara kadar MMP-9 dan rasio netrofil-limfosit pada penderita infark miokardium akut. Penelitian dilakukan secara potong lintang menggunakan sampel darah pasien dengan diagnosis kerja infark miokardium akut (IMA) (onset nyeri dada <24 jam) yang diambil dari beberapa rumah sakit di sekitar Kota Bandung dari periode Bulan Oktober–Desember 2012. Hubungan antara kadar MMP-9 dan rasio neutrofil leukosit dianalisis menggunakan uji korelasi Pearson. Analisis regresi linier digunakan untuk mengukur kekuatan pengaruh konsentrasi rasio neutrofil-limfosit pada kadar MMP-9. Sebanyak 37 pasien berusia 55,8 +11 tahun, dan 78% di antaranya adalah pria menjadi subjek dalam penelitian ini. Tujuh puluh enam persen sampel diantaranya merupakan pasien infark miokardium dengan elevasi ST dengan onset gejala 6 (3–14) jam. Rerata rasio limfosit-neutrofil adalah 5,24 (1Ïƒ ±2,4), dan kadar konsentrasi MMP-9 sebesar 370 (240–530) ng/ml. Uji Korelasi Pearson menunjukkan hubungan positif antara kedua variabel tersebut dengan nilai r=0,44 (p=0,003). Dari analisis regresi linier didapatkan rumus MMP-9= 40,87 (NLCR) + 211,3, yang digunakan untuk menunjukkan hubungan antara kadar MMP-9 dan rasio limfosit-netrofil. Terdapat hubungan positif antara kadar MMP-9 dan rasio neutrofil-limfosit pada pasien penderita IMA. Analisis regresi linier menunjukkan bahwa hanya rasio neutrofil-limfosit yang menjadi variabel prediktor independen kadar MMP-9. Kata kunci: Infark neutrofil akut, matriks-metaloproteinase 9 (MMP-9), rasio limfosit-neutrofil, remodeling ventrikel kiri